THE CORRELATION BETWEEN DENTAL MALOCCLUSION TO MIDLINE SHIFT AND BODY POSTURE OF JUNIOR HIGH SCHOOL STUDENTS - Parmasari, Wahyuni Dyah; Willianti, Enny; Theodora, Theodora (Indonesian Journal of Dentistry, 2025)
Background: The number of teenagers standing up straight according to normal posture is minimal. This results in it becoming a habit, so the body posture is not ideal in adolescence when the growth pattern is still ongoing. Early detection and intervention can help mitigate the impact of these issues on the student’s overall health, function, and quality of life. Methods: The design of this research is a cross-sectional and analytic observation. 70-person respondents were 1st-grade students of Junior High School 56 Surabaya. Outcome: In this study, the p-value obtained, was 0.06, a significant difference between the incidence of malocclusion in midline shift and body posture. Conclusion: There is a correlation between dental malocclusion to midline shift and body posture.